Auditory perception of biodiversity by human listeners - Grinfeder, Elie; Sueur, Jérôme; McWalter, Richard; Apoux, Frédéric; Lorenzi, Christian (Frontiers in Psychology, 2025)
IntroductionThis study explored human auditory capacity to evaluate the number of biological sound sources in natural soundscapes.MethodsThis was achieved by measuring the ability of human participants to judge the number of birds when listening to soundscapes generated by an engineering algorithm that controlled for bird abundance, species richness, level disparities between songs, bird behavior and background noise.Results and discussionAlthough often inaccurate, numerosity judgments were generally affected by the number of birds, demonstrating sub-optimal sensitivity to biodiversity in humans. Numerosity judgments were robust to low-intensity background sounds, and higher when between-species acoustic disparities were introduced, suggesting that grouping mechanisms contribute to biodiversity perception.